Parâmetros biológicos de Chrysoperla externa (Hagen) alimentada com presas criadas em híbridos de milho Bt e dieta com Bacillus thuringiensis (Berliner) - Ulhôa, João Luís Ribeiro (2015)
To know the impact of Bacillus thuringiensis (Berliner) upon the natural enemies is a challenge to compatibility of the strategies of the integrated pest management. Thus, the effect of the B.thuringiensis present in bioinsecticides Agree®, DipelWG® and Xentari® of Bt proteins on cultivars of transgenic corn DKB390PRO (VTPRO) and 2B587HX (RI) on adults and larvae of Chrysoperla externa (Hagen), respectively, was evaluated. Also, the feeding preference of the larvae of the predator for the nymphs of Schizaphis graminum (Rondani) and third-ínstar caterpillars of Spodoptera frugiperda (J.E. Smith) fed the transgenic corn DKB390PRO (VTPRO) and its isohybrid was evaluated. The biopesticides at their maximum dosage were added to the diet of the adults of the lacewings evaluating the oviposition, egg survival and longevity. It was observed that oviposition was influenced by the tested proteins, obtaining increased fecundity when adults were fed diet containing bioinsecticide. The egg survival was of 76%, longevity was not influenced at all. For the larvae fed the preys coming from Bt plants, consumption, development time, egg survival, longevity of adults and length of larvae were evaluated. No differences were found in the evaluated parameters, when the larvae of C. externa were fed the aphid reared on the hybrids DKB390PRO (VTPRO), its isohybrid DKB390 and conventional DKB399; 2B587HX (RI), its isohybrid 2B587 and conventional 30A68m. For larvae of C. externa when fed caterpillars of S. frugiperda raised on the corn Bt DKB390PRO (VTPRO) and 2B587HX (RI), no differences in consumption, development time, egg survival and adults’ longevity were found. As regards the length of the larvae of C. externa, no significant differences were detected, obtaining insects within the standard of the species. Relative to the standard feeding preference in the three instars of larvae of C. externa, also no significant differences were detected when nymphs of S. graminum, third instar caterpillars of S. frugiperda raised on plants of the evaluated corn cultivars were utilized as a food.